2016
DOI: 10.1002/jnr.23802
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress in early life as a predisposing factor for the development of chronic pain: Clinical and preclinical evidence and neurobiological mechanisms

Abstract: A wealth of research over the past 2 decades has expanded our understanding of the impact of early-life adversity on physiological function and, consequently, health and wellbeing in later life. Early-life adversity increases the risk of developing a number of disorders, such as chronic pain, fibromyalgia, and irritable bowel syndrome. Although much of the research has examined the impact of physical maltreatment, an increasing number of studies have been published over the past few years examining the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(152 citation statements)
references
References 155 publications
10
135
0
7
Order By: Relevance
“…The neurobiological mechanisms underlying the relationship between early-life stress and development of chronic pain are unclear, however, clinical and preclinical data suggested a key role for some neuro-
biological substrates, e.g . the hypothalamic-pituitary-adrenal axis, neurotransmissions (monoaminergic, opioidergic, endo-
cannabinoid) and immune systems [45-47]. In this regard, Interestingly, in maternal separation, one of the most commonly used models of early-life stress, Ploj and colleagues reported altered expression of the endogenous opioids dynorphin and enkephalin in the hypothalamus, substantia nigra, amygdala, and periaqueductal gray key brain areas in the modulation of emotional and nociceptive processes [48].…”
Section: Life Stressful Events and Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurobiological mechanisms underlying the relationship between early-life stress and development of chronic pain are unclear, however, clinical and preclinical data suggested a key role for some neuro-
biological substrates, e.g . the hypothalamic-pituitary-adrenal axis, neurotransmissions (monoaminergic, opioidergic, endo-
cannabinoid) and immune systems [45-47]. In this regard, Interestingly, in maternal separation, one of the most commonly used models of early-life stress, Ploj and colleagues reported altered expression of the endogenous opioids dynorphin and enkephalin in the hypothalamus, substantia nigra, amygdala, and periaqueductal gray key brain areas in the modulation of emotional and nociceptive processes [48].…”
Section: Life Stressful Events and Chronic Painmentioning
confidence: 99%
“…Moreover, Alexander and colleagues reported that stress potentiates nerve injury-induced tactile allodynia through a mechanism involving glucocorticoids acting at glucocorticoid receptors and glutamate receptor-mediated extracellular signal-regulated kinase (ERK) activation in dorsal horn neurons suggesting that these pathways converge to cause central sensitization [42]. Epigenetic alterations may also represent one of the key mechanisms underlying the development of chronic pain in later life [43, 47, 49-51]. …”
Section: Life Stressful Events and Chronic Painmentioning
confidence: 99%
“…These variables include prevailing cultural beliefs about the experience and expression of pain and suffering, 10,36,38,78 the medicolegal context within which the injury occurs, 21,37,85 the quality of social support, 90 and other life stressors (both recent and earlier in life). 15 Importantly, the extent to which these factors are either resiliencies or vulnerabilities likely varies by context, such that they may be a vulnerability under one condition and protective under another. 1 Take, for example, auto insurance coverage as a factor: adequate financial means to afford appropriate insurance coverage provided (or perceived to be provided) under a supportive client-insurer relationship may facilitate the patient's resumption of a satisfactory life trajectory.…”
Section: Diatheses In the New Modelmentioning
confidence: 99%
“…[185] However, ELS can be difficult to quantify and many studies do not control for the nature, frequency or duration of exposure. [27] iii) type of ELS. This can influence the brain region affected and the behavioral outcome.…”
Section: Contributing Factorsmentioning
confidence: 99%
“…Increased inhibition is reflected by either an increased threshold (if utilizing a protocol with a variable test stimulus) or reduced pain intensity (fixed test stimulus). [101; 142; 156; 222] In preterm born (24)(25)(26)(27)(28)(29)(30)(31)(32) weeks GA) children, CPM was enhanced in those with fewer painful procedures in NICU (n=6), but absent in a 'high-pain' group (n=7) with longer NICU stay and mechanical ventilation. [72] However, this study was performed at 8-11 years of age when descending modulation is less effective, [189] and evaluation at older ages is required.…”
Section: Analgesia and Sedation In Nicumentioning
confidence: 99%